A baurusuchid yearling (Mesoeucrocodylia, Crocodyliformes), from the Adamantina Formation, Bauru Group, Upper Cretaceous of Brazil. (2nd November 2022) - Martins dos Santos, Daniel; Miloni Santucci, Rodrigo; Maia de Oliveira, Carlos Eduardo; Brandalise de Andrade, Marco
ABSTRACT: Occurrences of young and immature individuals, relatively rare in the fossil record, are important due to the great amount of morphological and evolutionary information they reveal about a lineage's development. Although crocodylomorphs are the most abundant terrestrial vertebrates found in the Bauru Basin, southeastern Brazil, even outnumbering dinosaurian materials, much remains to be understood about their anatomy, ecology, and ontogeny. Egg fragments, nests and nesting sites attributed to Baurusuchus have been previously described, but unfortunately none of these yielded embryonic or hatchling remains. Here, we describe, for the first time, skeletal material of a small notosuchian yearling, recovered from the Adamantina Formation, with osteological features consistent with a baurusuchid affinity. We provide and discuss osteological and histological evidence of its ontogenetic stage, revealing morphological characters distinct from most adult forms, including conspicuous centro-parapophyseal laminae and developed ventral keels. Computerised tomography data also allowed for the identification of incipient ossification and a novel ontogenetic feature in the diminishing volume of the frontal´s internal recesses. Similar materials will increase our understanding of notosuchian ontogeny and diversity, thus requiring growth characters to be integrated into future phylogenies.